Povezanost karakteristika sile vuce merene plivanjem u mesti rezultata na 50m kraul kod plivaca: Novi aspekt testiranja - Dopsaj, M.; Matkovic, I.; Zdravkovic, I. (Facta Universitatis: Series Physical Education and Sport, 2000)
This study tries to define the relationship between 50m freestyle competition velocity in swimmers (criterion variable) on the one hand, and basic mechanical characteristics of pulling force as Fmax on the other, as well as impulse of force (ImpF) and rate of force developement (RFD) measured by tethered swimming test (Tethswim) at maximal intesity for 20 seconds (system of predictor variables). The sample consisted of 8 YU male freestyle sprinters, and the test was realised by a high-resolution tensiometric dynamometer (100 kHz) and a PC hardware-software system (ProIng). The recording of the realized pulling force yielded the averages of its maximal value (avgFmax5 to 20), its increment (avgRFD5 to 20) and its impulse (avgImpF5 to 20) for a single stroke in 5, 10, 15 and 20 s. The Backward Elimination criterion was used in Multiple Regression Analysis (MRA). The results of the MRA showed that the predictor system yielded a model structure of the variables avgImpF5, avgImpF10 and avgImpF20 and avgRFD20 that explained the criterion (V50comp) at a very high level of 96.4% of the common variance (F = 259.76, p = 0.000). The results indicate that when Tethswim is used in top sprinters, it seems more adequate to analyze/observe the values of avgImpF and stroke RFD than Fmax. They are mechanical characteristics and as such better describe sprinters' achievements.